Potret Minat Menulis Artikel Ilmiah Mahasiswa Tadris Matematika: Analisis Pengaruh Penggunaan Artificial Intelligence - Sarassanti, Yumi; Sulisti, Hidayu; Wahidah, Andina Nurul (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyze the effect of Artificial Intelligence (AI) use on the interest in writing scientific articles among mathematics education students. The research method used was a quantitative approach with an ex post facto design. The sample consisted of 29 students from the Mathematics Education Study Program, selected using purposive sampling. The research instruments consisted of a questionnaire on AI usage and a questionnaire on interest in writing scientific articles, both of which had been tested for validity and reliability. Data analysis was performed using simple linear regression. The results indicate that the use of AI significantly influences the interest in writing scientific articles among mathematics education students, with a significance level of 0.000 < 0.05 and a coefficient of determination of 62%. This suggests that the use of AI makes a significant contribution to enhancing the writing interest of mathematics education students. Consequently, the use of AI can serve as an alternative strategy for fostering a culture of scientific writing among students.